Association between Propionibacterium acnes and frozen shoulder: a pilot study. Issue 4 (October 2014) - Bunker, Tim D; Boyd, Matthew; Gallacher, Sian; Auckland, Cressida R; Kitson, Jeff; Smith, Chris D
Background: Frozen shoulder has not previously been shown to be associated with infection. The present study set out to confirm the null hypothesis that there is no relationship between infection and frozen shoulder using two modern scientific methods, extended culture and polymerase chain reaction (PCR) for bacterial nucleic acids. Methods: A prospective cohort of 10 patients undergoing arthroscopic release for stage II idiopathic frozen shoulder had two biopsies of tissue taken from the affected shoulder joint capsule at the time of surgery, along with control biopsies of subdermal fat. The biopsies and controls were examined with extended culture and PCR for microbial nucleic acid. Results: Eight of the 10 patients had positive findings on extended culture in their shoulder capsule and, in six of these, Propionibacterium acnes was present. Conclusions: The findings mean that we must reject the null hypothesis that there is no relationship between infection and frozen shoulder. More studies are urgently needed to confirm or refute these findings. If they are confirmed, this could potentially lead to new and effective treatments for this common, painful and disabling condition. Could P. acnes be the Helicobacter of frozen shoulder?